An investigation into the use of music as potential auditory enrichment for moloch gibbons (Hylobates moloch). Issue 4 (3rd June 2013) - Wallace, Emma K.; Kingston‐Jones, Mark; Ford, Matthew; Semple, Stuart
Abstract The use of music as enrichment has rarely been explored in zoos, despite evidence that music has a positive effect on a range of laboratory housed animals. In this study of moloch gibbons, Hylobates moloch, at Howletts Wild Animal Park (Kent, England), instrumental classical music was played to eight individuals in two family groups. Music was played 7 hr a day during three of six study weeks for each group, alternating with control weeks in which no music was played. In focal watches, data were recorded on a measure of activity, brachiation, and on two rates of affiliative behavior, giving and receiving grooming. In addition, to assess potential impacts on emotional state, data were recorded on self‐scratching and self‐grooming, two widely used indices of anxiety or stress. Analyses were carried out for each individual separately, as previous studies of primates indicate animals may differ in their response to enrichment. Results revealed little evidence for effects of music on gibbons' behavior. During the music compared to control weeks, the adult male from one group showed higher rates of self‐scratching and higher durations of both self‐grooming and grooming others. The adult female from the same group was groomed more during the music weeks than control weeks. For the six other animals, no significant differences in behaviors were seen between music and control conditions. Our findings suggest music may not be an effective enrichment for captive gibbons, and further highlight the importance of considering individual differences when assessing the effects of potential enrichment. Zoo Biol. 32:423–426, 2013. © 2013 Wiley Periodicals Inc.